Effects of composition and temperature on energy storage properties of (Pb, La)(Zr, Sn, Ti)O3 antiferroelectric ceramics. Issue 14 (1st October 2017) - Zhang, Qingfeng; Dan, Yu; Chen, Jian; Lu, Yinmei; Yang, Tongqing; Yao, Xi; He, Yunbin
Abstract: In this work, the effects of Zr 4+ addition on the phase structure and energy storage properties of (Pb0.97 La0.02 )(Zrx Sn0.945−x Ti0.055 )O3 (PLZST) antiferroelectric (AFE) ceramics were investigated, aiming to optimize the composition for enhanced energy storage properties. Due to the substitution of Zr 4+ with larger ion radius for Sn 4+, the tolerance factor of PLZST AFE ceramics decreased and thus the AFE state transformed gradually from tetragonal phase to orthorhombic phase with higher ferroelectric-antiferroelectric phase switching electric field ( E A ) with increasing Zr 4+ content from x=0.65–0.85. The increase of E A led to the improvement of recoverable energy density ( U re ) from 3.18 J/cm 3 (x=0.65) to 4.38 J/cm 3 (x=0.8). However, when Zr 4+ content was more than 0.8, the U re decreased from 4.38 J/cm 3 to 4.12 J/cm 3 (x=0.85) due to the reduction of the saturation polarization. The best energy storage properties were achieved in PLZST orthorhombic AFE ceramic with Zr 4+ content of x=0.8, which exhibited a maximum U re of 4.38 J/cm 3 and very small U re variation (<2.1%) in the range of 30–90 °C. The good temperature stability was attributed to the high Curie temperature of the ceramic which stabilized the AFE phase in a wide temperature range. The high energy storage density and good temperature stability demonstrate that (Pb0.97 La0.02 )(Zr0.8 Sn0.145 Ti0.055 )O3 antiferroelectric ceramic is a promising material for developing high-performance pulse power capacitors usable in wide temperature range.